(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Enzyme-linked immunosorbent assay (ELISA) is one of the most widely used immunological methods in modern laboratory diagnostics. This method is characterized by high sensitivity and specificity and plays an important role in the diagnosis of various infectious, autoimmune, endocrine, and oncological diseases. The present review article analyzes the theoretical basis of ELISA, its diagnostic potential in clinical practice, major advantages, and existing limitations based on contemporary scientific literature. The comprehensive application of ELISA in clinical laboratory practice enables early disease detection, effective monitoring, and evaluation of therapeutic efficacy.